Prognostic value of peripheral blood neutrophil-to-lymphocyte ratio and platelet-to-lymphocyte ratio in patients with gastric cancer - ZHANG Le, LI Wei, HUANG Zeping, WANG Wenjie, CHEN Xiao (Zhongguo linchuang yanjiu)
Objective To determine the predictive value of peripheral blood neutrophil-to-lymphocyte ratio (NLR) and the platelet-to-lymphocyte ratio (PLR) in the prognosis of patients with gastric cancer. Methods A retrospective analysis was conducted on the medical records of 272 gastric cancer patients who met the criteria and were treated at the Second Hospital of Lanzhou University from January 1, 2016, to December 31, 2017. The optimal diagnostic cut-off values for NLR and PLR were determined using X-tile software, according to which patients were divided into high and low NLR groups, high and low PLR groups, respectively, and the clinical data were compared and analyzed. The Cox proportional-hazards model was used to evaluate risk factors for overall survival (OS) and progression-free survival (PFS). Kaplan-Meier method was used to conduct survival analysis, while log-rank test was used to evaluated the differences. Results The optimal diagnostic cutoff values for NLR and PLR were found to be 2.01 and 121.91, respectively. Based on these cutoff values, patients were classified into a low NLR group (≤2.01,n= 120) and a high NLR group (＞2.01,n= 152), as well as a low PLR group (≤121.91,n= 115) and a high PLR group (＞121.91,n= 157). The low NLR group showed statistically significant differences in body mass index (BMI), tumor stage, white blood cell count (WBC), lymphocyte count (LYM), neutrophil count (NE), and carcinoembryonic antigen (CEA) compared to the high NLR group (P ＜0.05). The low PLR group exhibited significant differences in gender, maximum tumor diameter, tumor stage, hemoglobin (Hb), red blood cell count (RBC), platelet count (PLT), LYM, NE, and carbohydrate antigen 125 (CA125) compared to the high PLR group (P ＜0.05). Both univariate and multivariate Cox analyses indicated that high NLR and high PLR were risk factors affecting OS and PFS in gastric cancer patients (P ＜0.05). Kaplan-Meier survival analysis demonstrated that the high NLR group had lower OS (68 months vs 71 months,HR= 3.163， 95% CI：1.971-5.075， P ＜0.01) and PFS (67 months vs69.5 months,HR= 3.078， 95% CI：1.917-4.941，P ＜0.01)compared to the low NLR group, and similarly, the high PLR group had lower OS (67 months vs74 months,HR= 2.707，95% CI：1.685-4.350 ，P ＜0.01) and PFS (65 months vs73 months,HR= 2.718， 95% CI：1.691-4.367，P ＜0.01) compared to the low PLR group. Conclusion High NLR (＞2.01) and high PLR (＞121.91) indicate poor prognosis in gastric cancer patients and can serve as prognostic indicators for gastric cancer.